2017
DOI: 10.18632/aging.101199
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MiRNAs as biomarkers of gait speed responses to aerobic exercise training in obese older adults

Abstract: Gait speed is a useful predictor of adverse outcomes, including incident mobility disability and mortality in older adults. While aerobic exercise training (AEX) is generally an effective therapy to improve gait speed, individual responses are highly variable. Circulating microRNAs (miRNAs) may contribute to inter-individual changes in gait speed with AEX. We examined whether plasma miRNAs are associated with gait speed changes (dGaitSp) in 33 obese older adults (age: 69.3±3.6 years, BMI: 34.0±3.1 kg/m2, 85% w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 81 publications
(68 reference statements)
0
16
0
Order By: Relevance
“…Specifically, circulating miR-1, miR-133a, miR-133b, miR-139, miR-143, miR-181b, miR-206, miR-208b, miR-214, miR-223, miR-330, miR-338, miR-485, miR-509, miR-517a, miR-518f, miR-520f, miR-522, miR-553, and miR-888 were found increased, while miR-30b, miR-106a, miR-146a, miR-151, miR-221, miR-652 were decreased after an acute exercise (Banzet et al, 2013;Nielsen et al, 2014;Cui et al, 2016;Silva et al, 2017). , and miR-766 were decreased after a chronic exercise (Baggish et al, 2011(Baggish et al, , 2014Nielsen et al, 2014;Zhang et al, 2017b). Circulating miR-21, miR-146a, miR-221, miR-222 were increased in response to both acute and chronic exercise (Baggish et al, 2011).…”
Section: Discussionmentioning
confidence: 97%
“…Specifically, circulating miR-1, miR-133a, miR-133b, miR-139, miR-143, miR-181b, miR-206, miR-208b, miR-214, miR-223, miR-330, miR-338, miR-485, miR-509, miR-517a, miR-518f, miR-520f, miR-522, miR-553, and miR-888 were found increased, while miR-30b, miR-106a, miR-146a, miR-151, miR-221, miR-652 were decreased after an acute exercise (Banzet et al, 2013;Nielsen et al, 2014;Cui et al, 2016;Silva et al, 2017). , and miR-766 were decreased after a chronic exercise (Baggish et al, 2011(Baggish et al, , 2014Nielsen et al, 2014;Zhang et al, 2017b). Circulating miR-21, miR-146a, miR-221, miR-222 were increased in response to both acute and chronic exercise (Baggish et al, 2011).…”
Section: Discussionmentioning
confidence: 97%
“…They may act as tumour suppressors or oncogenes by regulating gene transcription [17,18]. It has been shown that circulating miRNAs may act as biomarkers of gait speed in obese adults [19] or have a prognostic role in cancer [20]. More recently, several articles confirmed that plasma miRNAs could be biomarkers of RCC, such as miR-144À3p and miR-210 [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Several miRs have been proposed as potential biomarkers of sarcopenia. Among them, circulating miR-21, miR-134a, miR-133 and miR-206 have diagnostic and/or prognostic potential due to their correlations with physical capacity [ 20 ]. However, their associations with indexes of sarcopenia in respiratory diseases are not known.…”
Section: Introductionmentioning
confidence: 99%